Reciprocal longitudinal effects between sense of school belonging and academic achievement: quasi-experimental estimates using United States primary school data - Sakellariou, Chris (Frontiers in Psychology, 2025)
This study investigates the bidirectional relationship between earlier sense of school belonging and later academic achievement in schoolchildren at grades 4 and 5 in US schools, using ECLS-K:2011 longitudinal data. Two alternative estimation methods were used, both addressing biases due to endogenous covariates. The findings (sample size > 8,000 observations) provide strong evidence that (1) the dominant effect is from sense of school belonging to achievement, where lower bound effect sizes are substantially larger than those reported in correlational studies; and (2) in the opposite direction biases are small, and bias-corrected effect estimates are generally in line with the multiple regression estimates. The findings also provide suggestive evidence of larger effects for girls compared to boys in the direction from sense of school belonging to achievement scores. The study's findings provide useful insights into the potential impact of school-based interventions.